Digital evolution and emerging revenue management practices: evidence from Aegean airlines distribution channels. (6th May 2021) - Katsoni, Vicky; Poulaki, Ioulia
Abstract : Purpose: The rapid digital transformation (DX) that airlines experienced during the past decade has been proven to be the driving force of significant benefits for the airlines when it comes to cost reduction, branding and revenue opportunities when passengers purchase tickets and ancillaries directly from their websites. This paper aims to contribute empirically to the theoretical approaches of DX and revenue management (RM) with the investigation of the Aegean airlines DX progress, focusing on emerging RM practices and digital distribution channels. Design/methodology/approach: A content analysis of the airlines' website and social media performance is used to note the current situation combined with previous and upcoming developments. Evaluation of the company's digitalization progress is approached by using a combination of two selected DX models, the digital transformation maturity (DTM) concept and the technology acceptance model (TAM). Findings: The analysis of qualitative and quantitative secondary data provided by the Aegean airlines indicates that the adoption of a digital evolution marketing plan, enriched with emerging RM practices, is leading to the increase of the bookings coming from the airline's direct distribution channels (Web & Apps) over those from intermediaries (GDSs). Consequently, Aegean airlines' DX progress favors cost reduction and revenue increase at the same time. Originality/value: DX model-based airline steps combined with direct versus indirect ticket purchase pattern compose a tool to evaluate the airline digitalization progress toward revenue integrity and product customization, as the latest trend in customer-centric strategy of businesses and customer relationship management (eCRM). Abstract : 数字化改革和新兴收益管理措施：以Aegean 航空分销渠道为例 研究目的: 近十年来的快速数字化改革（DX）证实了航空体验成为航空公司在降低成本、品牌效应、以及收益机会的时候显著受益的驱动因素, 这体现在当乘客通过网站购买飞机票和附加服务的时候。本论文旨在以Aegean航空DX进展为实例, 以事实来验证DX和收益管理（RM）的理论论断, 尤其在新兴RM措施和数字化分销渠道方面。 研究设计/方法/途径: 本论文采用文本分析航空网站和社交媒体表现的方法, 以展示结合过去和未来发展的目前情况分析。本论文通过结合两种DX模型, 数字化改革成熟概念（DTM）以及科技接受模型（TAM）, 对该航空公司的数字化进程进行评估。 研究结果: 本论文对Aegean航空公司的定量和定性的分析结果表明, 数字化改革营销计划, 结合新兴RM措施, 能够增加航空公司直接分销渠道（网站&APP）的订单收益, 相较于中间分销渠道（GDS）。因此, Aegean航空公司DX进程同时也降低了成本和增加了收益。 研究原创性/价值: DX模型航空业措施, 结合直接vs间接售票模式, 能够评估航空业数字化进程改进收益情况和产品定制化的有效工具, 这作为以客户为核心的商业战略和客户关系管理（eCRM）最潮流的趋势。